Fast diagnostic of osteoporosis based on hair analysis using LIBS technique. (May 2022) - Cherni, Imen; Nouir, Rihem; Daoud, Fatma; Hamzaoui, Sami; Ghalila, Hassen
Highlights: Elaboration of new approach more reachable, especially for developing country, becomes necessary for the diagnose of the osteoporosis pathology. Laser induced break spectroscopy (LIBS) applied on hair samples is proposed as a promising approach. The correlations between calcium and sodium lines with disease (BMD) make these two elements as reliable biomarkers. Ability to cluster between three groups i.e., osteoporotic, osteopenic and healthy using these two biomarkers are made possible. Abstract: Currently, the reference method for the diagnose of the osteoporosis pathology is the Dual energy X-ray Absorptiometry (DXA) technique which assesses Bone Mineral Density (BMD). As a major public health problem, classified as such by the World Health Organization, it is necessary to develop new techniques that are more accessible, especially for developing countries. The objective of this work is to propose a new technique based on laser-induced breakdown spectroscopy (LIBS) using calcium and sodium in hair as a biomarker for the detection of osteoporosis pathology. The study involved 90 women aged 50 to 70 years divided in three groups, thirty women with osteoporosis, thirty women with osteopenia and thirty healthy women. The application of LIBS technique on their hair to correlate calcium and sodium lines with T-scores allows a quick and cheap screening of the disease. The results showed strong correlations between calcium lines and disease. We noted a negative correlation between the intensity of calcium and sodium lines. In addition to these results, we show that we were able to cluster the three groups using the emission lines of these two elements. All these results support the idea that the use of LIBS applied to hair to evaluate calcium and sodium elements as effective biomarkers for the detection of osteoporosis is a promising approach.